2022
DOI: 10.1002/pon.5931
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of self‐compassion and psychological outcomes in cancer patients

Abstract: Objectives The protective role of self‐compassion in cancer patients' psychological outcomes has been confirmed. However, using a composite score of self‐compassion, previous research could not clarify how distinct components of self‐compassion may mutually interact. This study, using a person‐centred approach, aimed to identify profiles of self‐compassion in cancer patients and examined the associations of self‐compassion profiles with sociodemographic and medical variables and psychological outcomes. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…self-judgement, isolation and over-identification) reported more symptoms of depression, anxiety and stress, regardless of their parenting efficacy. The robustness of the links between self-coldness and symptoms of psychological distress highlights the importance of this negative component of self-compassion and aligns with research finding greater self-compassion associated with less depressive symptoms among lung cancer patients ( Siwik et al, 2022 ) and with fewer depressive and anxiety symptoms in a mixed sample of cancer patients ( Wei et al, 2023 ). Self-coldness can manifest in unhelpful strategies that mothers employ in their parenting roles or more generally, such as over-identifying with, suppressing or avoiding their negative emotions; strategies shown to predict worse psychological symptoms among women receiving radiation therapy for breast cancer ( Guimond et al, 2020 ).…”
Section: Discussionsupporting
confidence: 74%
“…self-judgement, isolation and over-identification) reported more symptoms of depression, anxiety and stress, regardless of their parenting efficacy. The robustness of the links between self-coldness and symptoms of psychological distress highlights the importance of this negative component of self-compassion and aligns with research finding greater self-compassion associated with less depressive symptoms among lung cancer patients ( Siwik et al, 2022 ) and with fewer depressive and anxiety symptoms in a mixed sample of cancer patients ( Wei et al, 2023 ). Self-coldness can manifest in unhelpful strategies that mothers employ in their parenting roles or more generally, such as over-identifying with, suppressing or avoiding their negative emotions; strategies shown to predict worse psychological symptoms among women receiving radiation therapy for breast cancer ( Guimond et al, 2020 ).…”
Section: Discussionsupporting
confidence: 74%
“…30 Comparatively, oncology patients exhibit heightened empathetic care requirements in contrast to other departments such as Emergency and ICU. 31 Research suggests that nurses with elevated empathy levels are more adept at comprehending patient emotions, fostering harmonious nurse-patient relationships, bolstering personal ful llment, and mitigating professional burnout. 32 Studies further demonstrate the positive impact of nurses' empathy on VPTG.…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial research included in this Special Issue identifies individual resiliency factors, such as self‐compassion, in patients with cancer in Xi’An, China 19 and pilot studies are reported demonstrating the feasibility of written exposure therapy for posttraumatic stress disorder in Iranian women with breast cancer 20 and of acceptance and commitment therapy for parents of children with a haematological malignancy or a solid tumour. 21 Asuzu et al 22 report a pilot psychosocial intervention group in Nigeria that shows potential in supporting breast cancer patients.…”
Section: Overview Of the Special Issue Contentmentioning
confidence: 99%